2003
DOI: 10.1017/s0305000903005816
|View full text |Cite
|
Sign up to set email alerts
|

The use of grammatical morphemes reflecting aspect and modality by children with specific language impairment

Abstract: Children with specific language impairment (SLI) have well-documented problems in the use of tense-related grammatical morphemes. However, in English, tense often overlaps with aspect and modality. In this study, 15 children with SLI (mean age 5;2) and two groups of 15 typically developing children (mean ages 3;6 and 5;3) were compared in terms of their use of previously studied morphemes in contexts that more clearly assessed the role of aspect. The children's use of less frequently studied morphemes tied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 20 publications
0
35
0
1
Order By: Relevance
“…Previous studies of auxiliary be forms with TD children in this age range show percentages of use in obligatory contexts to be approximately 70% or higher (Leonard et al, 2003;Rice, Wexler, & Cleave, 1995). In each of these studies, these children were found to produce auxiliary is and are with higher percentages in obligatory contexts than the 5-year-old children with SLI with whom they were matched on mean length of utterance.…”
Section: Participantsmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies of auxiliary be forms with TD children in this age range show percentages of use in obligatory contexts to be approximately 70% or higher (Leonard et al, 2003;Rice, Wexler, & Cleave, 1995). In each of these studies, these children were found to produce auxiliary is and are with higher percentages in obligatory contexts than the 5-year-old children with SLI with whom they were matched on mean length of utterance.…”
Section: Participantsmentioning
confidence: 78%
“…In each of these studies, these children were found to produce auxiliary is and are with higher percentages in obligatory contexts than the 5-year-old children with SLI with whom they were matched on mean length of utterance. We accordingly set our selection criterion at 70% use, measuring degree of use through the auxiliary production probe task used by Leonard et al (2003) with 10 auxiliary is items and 10 auxiliary are items. Actions with toys and props were shown to children, and, as the action was occurring, the children were prompted to complete a declarative sentence beginning with either a singular or plural noun phrase as in "Tell me about the babies.…”
Section: Participantsmentioning
confidence: 99%
“…Specifically, children with SLI appear to have morphological deficits that are greater than their MLUs would typically predict (Leonard, Davis, & Deevy, 2007;Maillart & Parisse, 2006). Specific weaknesses within SLI verb morphology identified include the underuse of past tense -ed (Leonard et al, 2007) and past tense auxiliaries such as was and were (Leonard, Deevy, Miller, Charest, & Kurtz, 2003;Rice & Wexler, 1996), as well as inconsistent use of third person -s. In addition, children with SLI are more likely than TD peers to omit the nonfinite particle to, arguments in finite clauses, and the optional complementizer that (Owen & Leonard, 2006). Children with SLI show such marked morphology deficits that some have proposed them as a clinical marker for the condition (Rice, Wexler, & Hershberger, 1998).…”
mentioning
confidence: 99%
“…Children's use of auxiliary am was explored by adapting a probe task used by Leonard et al (2003) to elicit auxiliary is, are, and was. The general task makes use of a puppet theatre and 'shows' performed by characters.…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…To our knowledge, tasks of this sort have not yet been employed to elicit utterances requiring the use of first person verb forms such as auxiliary am. Indeed, studies that have examined auxiliary be forms in probes have focused instead on the morphemes is, are, was, and were (eg, Leonard et al, 2003).…”
Section: Introductionmentioning
confidence: 99%